2013
DOI: 10.1007/s00705-013-1880-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of doxycycline against dengue virus replication in vitro

Abstract: Doxycycline is an antibiotic derived from tetracycline that possesses antimicrobial and anti-inflammatory activities. Antiviral activity of doxycycline against dengue virus has been reported previously; however, its anti-dengue properties need further investigation. This study was conducted to determine the potential activity of doxycycline against dengue virus replication in vitro. Doxycycline inhibited the dengue virus serine protease (DENV2 NS2B-NS3pro) with an IC50 value of 52.3 ± 6.2 μM at 37 °C (normal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 33 publications
1
91
1
2
Order By: Relevance
“…It has been reported that these therapies could have activities beyond antimalarial activity, also against viral infectious agents. Surprisingly, in many cases, the administration of antibiotics alone or in combination with other antiviral agents showed significant antiviral activities against different types of viral infections [168][169][170][171]. Despite this evidence, the antiviral mechanisms of action have not been completely investigated.…”
Section: Antimicrobial Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that these therapies could have activities beyond antimalarial activity, also against viral infectious agents. Surprisingly, in many cases, the administration of antibiotics alone or in combination with other antiviral agents showed significant antiviral activities against different types of viral infections [168][169][170][171]. Despite this evidence, the antiviral mechanisms of action have not been completely investigated.…”
Section: Antimicrobial Drugsmentioning
confidence: 99%
“…This result was confirmed by Rothan and colleagues, who evaluated the replication rate of DENV in an in vitro model of infected cells. They reported that DOX inhibited DENV replication in vitro by reducing viral protease activity and entry into host cells [168]. The same research group determined the inhibitory effects of DOX against CHIKV as well as its possible effect on the virus life cycle in Vero cells when the virus and the drug were administered concurrently to the cells.…”
Section: Doxycyclinementioning
confidence: 99%
See 1 more Smart Citation
“…The docking methodology was validated using the standard ligands, pinostrobin (1) and 4-hydroxypanduratin A (2), each representing the noncompetitive and competitive inhibitors, respectively. Previous in vitro studies had highlighted the inhibitory potentials for compounds 3, 4 and 5 (Table 1), with compound 3 reported to be non-competitive (Rothan et al 2014b(Rothan et al , 2013. Therefore, the current docking study was conducted not only to determine the ligand poses in the binding sites and the interactions involved, but also to determine the sites to which compounds 4 and 5 were bound and to further validate the inhibitory characteristic of compound 3.…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotics such as doxycycline (3) and rolitetracycline (5) showed significant inhibitory activity against NS2B-NS3 protease of DENV-2 (Rothan et al 2014b(Rothan et al , 2013. Furthermore, previous finding had shown that non-steroidal anti-inflammatory drug (NSAID), such as meclofenamic acid (4), was not only used to treat symptoms of dengue infections (Kumar et al 2015) but also to inhibit the NS2B-NS3 protease (Rothan et al 2013).…”
Section: Introductionmentioning
confidence: 99%